Synthesis and catalytic studies of barium and strontium exchanged ETS-10 in knoevenagel condensation reaction - Noor Hazzarita Abdullah, 1989-; Mustaffa Shamsuddin, supervisor; Fakulti Sains (2012)
Thesis (Sarjana Sains (Kimia)) - Universiti Teknologi Malaysia, 2012